Stigma and attitudes towards restrictive practices in psychiatry among psychology students: a network and path analysis study in an Italian sample. (2nd January 2022) - Solmi, Marco; Granziol, Umberto; Boldrini, Tommaso; Zaninotto, Leonardo; Salcuni, Silvia
Abstract: Background : People suffering from mental disorders are affected by public stigma in many areas of daily life, including mental health services. Stigma among mental health professionals needs to be addressed. Aims : This study explores the path leading to attitudes toward seclusion and restraint practices among future mental health professionals, considering the complex interplay among demographic variables, personality, stigma, and experience in psychiatric services. Method: Network analysis and Structural Equation Modeling were used to explore 1512 Psychology students. The survey instrument included a form for demographic and academic variables, the Attribution Questionnaire-9, the Ten Items Personality Inventory, and few questions exploring attitudes toward open-door and restraint-free policies in Psychiatry. Results: The personality trait of Openness and previous experience with psychiatric patients resulted to play a positive effect on stigma. Openness was also associated with a better disposition towards restraint-free policies. Conversely, higher levels of stigma predicted a negative attitude toward no restraint, decreasing the positive effect of Openness. Conclusions: In conclusion, some personality traits may be associated with lower levels of stigma and a more open view about treatment policies in Psychiatry. Direct educational or professional experience with patients suffering from mental disorders may be a crucial factor in reducing the risk of stigmatizing attitudes in future professionals.